Efficacy and tolerability of six-week extended dosing interval with tocilizumab therapy in a prospective cohort as remission maintenance in patients with rheumatoid arthritis. Issue 3 (4th May 2018) - Kikuchi, Jun; Kondo, Tsuneo; Shibata, Akiko; Sakai, Ryota; Okada, Yusuke; Chino, Kentaro; Okuyama, Ayumi; Kurasawa, Takahiko; Takei, Hirofumi; Amano, Koichi
Abstract: Objectives: To prospectively evaluate the efficacy and tolerability of a six-week extended dosing interval with tocilizumab (TCZ) in patients with rheumatoid arthritis (RA) in sustained remission. Methods: Patients who received over six doses of intravenous TCZ in clinical remission (disease activity score [DAS] 28 – erythrocyte sedimentation rate [ESR] ≤ 2.6) maintained over 3 months between December 2013 and December 2015 were included. Flare was defined as DAS28-ESR >3.2 at two consecutive visits. Results: Twenty-five patients were enrolled; 87.5% achieved clinical remission at week 54 after six-week extension and 95.5% achieved a van der Heijde modified total Sharp score (ΔmTSS) ≤0.5. The Health Assessment Questionnaire Disability Index (HAQ-DI) did not increase during 54 weeks. HAQ-DI at baseline and ΔDAS28-ESR at week six positively correlated with increase in DAS28-ESR at week 54. ΔSwollen joint count at week six positively correlated with ΔmTSS at week 54. A total of 12 adverse events occurring in 10 patients did not lead to cessation of TCZ except for one case of recurrent lymphoproliferative disorder at week five. Conclusion: A six-week extended dosing interval of TCZ for patients with RA in sustained remission is proposed as an acceptable treatment option for maintaining efficacy and tolerability.